2023
DOI: 10.1007/s00161-023-01208-w
|View full text |Cite
|
Sign up to set email alerts
|

Finite extension of accreting nonlinear elastic solid circular cylinders

Abstract: In this paper we formulate and solve the initial-boundary value problem of accreting circular cylindrical bars under finite extension. We assume that the bar grows by printing stress-free cylindrical layers on its boundary cylinder while it is undergoing a time-dependent finite extension. Accretion induces eigenstrains, and consequently residual stresses. We formulate the anelasticity problem by first constructing the natural Riemannian metric of the growing bar. This metric explicitly depends on the history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It was observed that the six known families of universal deformations are invariant under specific Lie subgroups of the special Euclidean group. There are also some recent studies of universal deformations and eigenstrains in accreting bodies [65][66][67]. There have also been studies of universal deformations in liquid crystal elastomers [68,69].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the six known families of universal deformations are invariant under specific Lie subgroups of the special Euclidean group. There are also some recent studies of universal deformations and eigenstrains in accreting bodies [65][66][67]. There have also been studies of universal deformations in liquid crystal elastomers [68,69].…”
Section: Introductionmentioning
confidence: 99%